I am reading the book Convex Optimization, and I don't understand why a $\max$ function is convex.

The function is defined as:

$$f(x) = \max(x_1, x_2, \dots, x_n)$$

The book offers the proof shown below:

for $0 \leq \theta \leq 1$

$$\begin{aligned} f(\theta x + (1 - \theta)y) &= \max_i \left( \theta x_i + (1 - \theta)y_i \right)\\ & \leq \theta \max_i x_i + (1 - \theta)\max_i y_i\\ &= \theta f(x) + (1 - \theta)f(y) \end{aligned}$$

However, I don't understand why the following inequality holds.

$$\max_i (\theta x_i + (1 - \theta)y_i) \leq \theta \max_i x_i + (1 - \theta)\max_i y_i$$


Fix $k\in \{1,\ldots,n\}$. We have $$\theta x_k + (1-\theta)y_k \leq \theta \max_i x_i + (1-\theta)\max_i y_i$$ because $x_k \leq \max_i x_i$, $y_k \leq \max_i y_i$, $\theta \geq 0$ and $1-\theta \geq 0$.

Since the statement above is true for any $k$ we have:

$$\max_k [\theta x_k + (1-\theta)y_k]\leq \theta \max_i x_i + (1-\theta)\max_i y_i.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.